1998
DOI: 10.1111/j.1469-8749.1998.tb15351.x
|View full text |Cite
|
Sign up to set email alerts
|

Reading ability and processing in Duchenne muscular dystrophy and spinal muscular atrophy

Abstract: Duchenne muscular dystrophy (DMD) is a fatal recessive X-linked muscular disease affecting about 1 in 3500 live-born human males, characterized by severe muscle degeneration and responsible for muscular weakness. *Correspondence to first nictbor at address nbotieWe analysed the reading avities and processing of 21 children.with Duchenne muscular dystrophy (DMD), 11 matched children suffering from spinal muscular atrophy (SMA) and 42 children receiving normal education. The principal result observed was that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
76
1
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(89 citation statements)
references
References 32 publications
4
76
1
8
Order By: Relevance
“…Single-word comprehension has been shown to be strong, 8,9,17 as has single word expression or picture naming, 6,9 although it is lower in younger children with DMD. 18 Some studies have demonstrated impaired verbal fluency, 8,17,19,20 whereas others do not; 6,9 the differences are probably due in part to impaired letter or phonemic fluency and intact category or semantic fluency.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Single-word comprehension has been shown to be strong, 8,9,17 as has single word expression or picture naming, 6,9 although it is lower in younger children with DMD. 18 Some studies have demonstrated impaired verbal fluency, 8,17,19,20 whereas others do not; 6,9 the differences are probably due in part to impaired letter or phonemic fluency and intact category or semantic fluency.…”
Section: Discussionmentioning
confidence: 99%
“…18 Some studies have demonstrated impaired verbal fluency, 8,17,19,20 whereas others do not; 6,9 the differences are probably due in part to impaired letter or phonemic fluency and intact category or semantic fluency. Tests of syntactic comprehension have shown compromised skills in some studies 9,17 but not in others 6 (although we have argued that poor performance was due less to not understanding grammatical rules than to the verbal load of the tasks, thus implicating immediate verbal span 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Children with DMD also have mental impairment, reflected in borderline or reduced scores in the full intelligence quotient and visuospatial tests (Wicksell, Kihlgren, Melin, & Eeg-Olofsson, 2004), visuomotor impairment (Marsh, 1972;Mehler, 2000), a reduction in verbal ability (Bresolin et al, 1994), and impairment in reading ability (Billard, Gillet, Barthez, Hommet, & Bertrand, 1998). Improvements in respiratory management and pharmacological drugs have increased the life expectancy of DMD children by almost a decade.…”
Section: Discussionmentioning
confidence: 99%